Scaling of Vertical Component of Seismic Ground Motion - ALMahdi, Fikrat; Fahjan, Yasin; Dogangun, Adem (Elsevier, 2020)
Three-dimensional time history analysis has become a demand for the majority of updated building codes. A vast literature has addressed the selecting and scaling of horizontal component of earthquake ground motion. Meanwhile, the scaling of vertical component has been less of a concern. This paper investigates the suggestion of using the same scaling factor of horizontal component of ground motion to scale its vertical counterpart. A data set consists of 6409 mainshock records with vertical and orientation independent geometric rotated (GMRotD50) response spectra with 5% damping is used. Even though ASCE7 - 16 among other international codes recommends to use the same scaling factor for horizontal component and its vertical counterpart, this paper shows that scaling factor of vertical component trends an extreme variation from its horizontal counterpart for various soil classes, different magnitudes and over a wide range of Joyner-Boore distances. Results illustrate that the ratio of vertical to horizontal scaling factors has a strong negative relationship with the ratio of vertical to horizontal peak ground acceleration. Earthquake magnitude has no significant role on the ratio of vertical to horizontal scaling factors. A gradual increase is observed in the studied ratio over a wide range of Joyner-Boore distances. The paper ends up with simplified equations to calculate the scaling factor of vertical component in regards with the scaling factor of its GMRotD50 horizontal counterpart based on the (V/H)(PGA) ratio of the recorded components. Robust statistics manifest the goodness of the developed equations. (C) 2020 The Authors. Published by Elsevier B.V. on behalf of Faculty of Engineering, Alexandria University.
Keywords: Vertical ground motion; Scaling factor; Response spectrum; ASCE7-16; Eurocode 8